Mailing human papillomavirus self-sampling kits to women under-screened for cervical cancer improved detection in cervical cancer screening in a general population study in Japan - Yoko Nishimura; Motoki Matsuura; Noriko Terada; Sachiko Nagao; Hiroshi Shimada; Kyoko Isoyama; Masato Tamate; Masahiro Iwasaki; Tsuyoshi Saito (BMC, 2023)
Abstract Background One cause of the increase in cervical cancer rates in Japan is the long-term stagnation in the cervical cancer screening consultation rate. Therefore, improving the screening consultation rate is of urgent concern to reduce cervical cancer incidence. Self-collected human papilloma virus (HPV) tests have been successfully adopted in several countries, such as the Netherlands and Australia, as a measure of individuals who have not undergone cervical cancer screening in national programs. This study aimed to verify whether self-collected HPV tests presented an effective countermeasure for individuals who had not undergone the recommended cervical cancer screenings. Methods This study was conducted from December 2020 to September 2022 in Muroran City, Japan. The primary evaluated endpoint was the percentage of citizens who underwent cervical cancer screening at a hospital with positive self-collected HPV test results. The secondary endpoint was the percentage of included participants who were diagnosed with cervical intraepithelial neoplasia (CIN) or higher among those who visited a hospital and underwent cervical cancer screening. Results The included study participants were 7,653 individuals aged 20-50 years with no record of previous cervical cancer examination in the past 5 years. We mailed these participants information on self-administered HPV tests as an alternative screening procedure and sent the kit to 1,674 women who requested the test. Among them, 953 returned the kit. Among the 89 HPV-positive individuals (positive rate, 9.3%), 71 (79.8%) visited the designated hospital for an examination. A closer examination revealed that 13 women (18.3% of hospital visits) had a CIN finding of CIN2 or higher, among whom one each had cervical cancer and vulvar cancer, eight presented with CIN3, and three presented with CIN2; two cases of invasive gynecologic cancer were also identified. Conclusions We conclude that the self-collected HPV tests showed a certain efficacy as a measure of individuals who had not undergone the recommended cervical cancer screening. We devised ways to have the unexamined patients undergo HPV testing and ensure that HPV-positive individuals visited the hospital. Despite a few limitations, our findings suggest the effectiveness of this public health intervention.